3-[(2-Hydroxybenzyl)azaniumyl]propanoate monohydrate - Basu Baul, Tushar S.; Chaurasiya, Anurag; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The title compound, C10H13NO3·H2O, is a zwitterion hydrate with the zwitterion comprising a central ammonium group and a carboxylate residue. In the zwitterion, the hydroxybenzene and carboxylate groups are directed to the same side of the molecule and each orientated to place an O atom in a position to form an intramolecular ammonium-N-H...O hydrogen bond, each closing an S(6) loop. The three-dimensional architecture is stabilized by hydroxy-O-H...O(carboxylate), water-O-H...O(carboxylate) and ammonium-N-H...O(water) hydrogen bonds.